Hand, hand, fingers, thumb ebook - Perkins, Al (Bright & Early Books., 2011)
A madcap band of dancing, prancing monkeys explain hands, fingers, and thumbs to beginning readers.   Bright and Early Books are perfect for beginning beginner readers! Launched by Dr. Seuss in 1968 with The Foot Book , Bright and Early Books use fewer and easier words than Beginner Books. Readers just starting to recognize words and sound out letters will love these short books with colorful illustrations.